Tabot Ditinjau Dari Perspektif Hukum Islam - Amirullah, Muhammad Azrul; Septiyan Dwi Putra (SM Institute, 2025)
Indonesia is a country rich in culture, tribes, customs, food, and natural resources, making Indonesia one of the countries that the world counts in these matters. In addition to culture, tribes, customs, food, and natural resources, Indonesia is also named as a nation that adheres to the second largest Islamic religion in the world after Pakistan. This religion entered Indonesia around the 7th century AD, more specifically, during the period of the Bani Umayyah caliphate. This research uses a qualitative research methodology that emphasizes literature study to analyze the Ark tradition in Bengkulu, focusing on a comparative perspective on Ark activities when viewed from the perspective of Islamic Law. In the study of fiqh science, there is a rule that reads al-addah al-muhakkamah which is one of the rules of fiqh (Islamic law rules) which states that customs or habits that have been accepted and agreed upon by the community can be the basis or footing in determining the law. When viewed from the point of view of Islam, which has the ahlusunnah wal jama'ah belief.